2022
DOI: 10.1002/elps.202200147
|View full text |Cite
|
Sign up to set email alerts
|

Use of a solid‐state nanopore for profiling the transferrin receptor protein and distinguishing between transferrin receptor and its ligand protein

Abstract: A nanopore device is capable of providing single‐molecule level information of an analyte as they translocate through the sensing aperture—a nanometer‐sized through‐hole—under the influence of an applied electric field. In this study, a silicon nitride (SixNy)‐based nanopore was used to characterize the human serum transferrin receptor protein (TfR) under various applied voltages. The presence of dimeric forms of TfR was found to decrease exponentially as the applied electric field increased. Further analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…46,47 O'Donohue et al demonstrated the successful classification of the monomeric and dimeric forms of human serum transferrin receptor proteins through SSNs and confirmed the coexistence of both forms in a heterogeneous mixture. 48 The research findings of Yin et al exemplify the use of nanopores of varying diameters in the discrimination of ferritin and apo-ferritin, which display identical exterior structures and divergent interior structures. 49 Thus, it is evident that SSNs can be productively used in discriminating protein-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…46,47 O'Donohue et al demonstrated the successful classification of the monomeric and dimeric forms of human serum transferrin receptor proteins through SSNs and confirmed the coexistence of both forms in a heterogeneous mixture. 48 The research findings of Yin et al exemplify the use of nanopores of varying diameters in the discrimination of ferritin and apo-ferritin, which display identical exterior structures and divergent interior structures. 49 Thus, it is evident that SSNs can be productively used in discriminating protein-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the other study, Matthew O′Donohue et al. were able to distinguish the transferrin protein and its receptor populations by solid‐state nanopores [25] . Also, a solid‐state nanopore was used to quantify the aggregation of different proteins based on their non‐uniform charge distribution by Mitu C. Acharjee et al [26] …”
Section: Introductionmentioning
confidence: 99%
“…[23] For instance, the translocation of more than a million-protein using modified solid-state nanopores and a method for restoring clogged pores in real-time were investigated by Jugal Saharia et al [24] In the other study, Matthew O'Donohue et al were able to distinguish the transferrin protein and its receptor populations by solid-state nanopores. [25] Also, a solid-state nanopore was used to quantify the aggregation of different proteins based on their non-uniform charge distribution by Mitu C. Acharjee et al [26] Blood components such as Alpha-1 antitrypsin (AAT) play a critical role in preventing tissue breakdown by proteolytic enzymes. It protects the lungs from neutrophil elastase, an enzyme responsible for degrading elastin.…”
Section: Introductionmentioning
confidence: 99%